The importance of social media in building brand and corporate image - Król, Piotr (Funkcjonowanie e-biznesu. Zasoby, procesy, technologie, 2015)
The brand of a product is very important for its promotion and the sale of products, branding also provides many advantage both for consumers, as well as manufacturers.In the article the concept of brand is presented, establishing a brand, and the relationship between a brand and a product, background, Public Relations.In this paper, the author tries to define not only what the brand is, but also describe a spectrum what makes brand palpable. These questions are discussed using the example of Lodz’s entrepreneurs which uses social media to creates their own brand.